Madura Di Mata Media: Analisis Framing Atas Pemberitaan Konflik Dan Kekerasan - Khaireza Amien Nurrahman; Surokim (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This research stems from the debate about the role of national media in reproducing symbolic inequality between the center and the periphery through the practice of framing news about violence. Focusing on reporting on violence in Madura, this study examines how Kompas.com and Detik.com construct social meanings that have implications for representations of territory and collective identity. Drawing on Entman's framing theory, this study combines quantitative text analysis based on Voyant Tools with critical qualitative interpretation in a mixed-methods design. A total of 70 news articles, 35 each from Kompas.com and Detik.com published between 2023 and 2025, were analyzed. The findings indicate significant differences in framing strategies: Kompas.com tends to adopt thematic framing that links violence to broader social and cultural contexts, while Detik.com predominantly uses episodic framing that emphasizes crime and the chronology of events. This study argues that these differences are not neutral, but rather contribute to the construction of Madura as a symbolic space of conflict in national media discourse. Thus, this study offers a critical contribution to the study of media framing in Indonesia by highlighting how online journalistic practices can reproduce center periphery hierarchies while limiting public understanding of social complexities in peripheral areas.